Comparison of the Depression Disorder and Related Psychosocial Disorders Before and After Contracting COVID-19 in Women Attending Imam Khomeini Hospital Complex - Mamak Shariat; Nasrin Abedinia; Fatereh Momeni; Yasamin Soufi Enayati (Journal of Family and Reproductive Health)
Objective: The present study was conducted with the aim of comparing psychosocial disorders before and after contracting COVID-19 in women in the city of Tehran. Materials and methods: A retrospective descriptive-analytical study was conducted on 250 women who had recovered from COVID-19. The data were collected from the information registration system for COVID-19 patients in Tehran-Iran from the year 2019 until 2020. Data were collected using demographic questionnaires, The Hospital Anxiety and Depression Scale (HADS), The Billings and Moss Coping Strategies, Multidimensional Scale of Perceived Social Support (MSPSS), Mini-Mental State Examination (MMSE), Russell Loneliness Scale, Beck Scale for Suicide Ideation (BSSI), Female Sexual Function Index (FSFI), and Pittsburgh Sleep Quality Index (PSQI). Data analysis was performed using the analysis of covariance (ANCOVA). The SPSS-20 software was utilized for data analysis. Results: The results obtained in this study indicated that women who had more severe COVID-19 reported higher levels of depression and cognitive disorders and lower sexual tendencies after recovery compared to women with mild COVID-19. There was a significant difference in disease severity (from mild to severe) in psychological variables such as sleep and sexual disorders, depression, social support, and cognition before and after recovery from COVID-19 (p=0.0001). Conclusion: Due to severe fear and anxiety and other psychological disorders in people infected with Corona even after recovery from the disease, Psychologists should take measures for the relaxation and mental health of patients, such as consultations (online and by phone) for patients at home during quarantine, which will cause the patient to recover as quickly as possible and prevent mental disorders of the patients.